1990
DOI: 10.1111/j.1744-7348.1990.tb06609.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lodging and a paclobutrazol — chlormequat chloride mixture on the yield and quality of oilseed rape

Abstract: The effects of lodging and a plant growth regulator mixture on oilseed rape cv. Ariana were studied in three field experiments. Natural and artificially induced lodging treatments varying in time of imposition and severity were compared to a supported control. A mixture of paclobutrazol and chlormequat chloride was applied either as a spray or as paclobutrazol granules followed immediately by a chlormequat chloride spray.In 1987, severe lodging treatments reduced yield by up to 52%. Yield penalties varied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
(7 reference statements)
3
26
0
1
Order By: Relevance
“…Excessive use of nitrogen and phosphorus fertilisers result in severe lodging, which is the major cause of yield loss (Gill, 1992). Crops that were naturally or artificially lodged were more susceptible to diseases and produced lower yields than crops that were mechanically supported or prevented from lodging by treatment with plant growth retardants (Baylis & Wright, 1990). Inhibitors of gibberellin biosynthesis, such as chlormequat chloride (Saini, Jolly & Singh, 1987) and paclobutrazol (Baylis & Huntley-Bull, 1991), have been used successfully to prevent lodging and increase seed and oil yields of brassica oilseed crops.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive use of nitrogen and phosphorus fertilisers result in severe lodging, which is the major cause of yield loss (Gill, 1992). Crops that were naturally or artificially lodged were more susceptible to diseases and produced lower yields than crops that were mechanically supported or prevented from lodging by treatment with plant growth retardants (Baylis & Wright, 1990). Inhibitors of gibberellin biosynthesis, such as chlormequat chloride (Saini, Jolly & Singh, 1987) and paclobutrazol (Baylis & Huntley-Bull, 1991), have been used successfully to prevent lodging and increase seed and oil yields of brassica oilseed crops.…”
Section: Introductionmentioning
confidence: 99%
“…At Giessen it was observed that by reducing the concentration of Toprex from 0.5 to 0.35 L· ha −1 in combination with Ortiva increased lodging. Baylis and Wright (1990) [15] also observed similar results after applying paclobutrazole on winter rapeseed. 1000-grain weight (TGW) is an important yield component because large seed is more valuable.…”
Section: Resultsmentioning
confidence: 57%
“…These treatments protected plants from severe lodging compared to the control treatment. Lodging caused mechanical damage to seeds during harvesting [15], and damaged seeds led to increased PV. Severely lodged cv.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared with its excellent growth regulation effects, the fungicidal effect of this chemical is actually rather minor Accordingly, paclobutrazol is used as an important plant growth regulator in most cases. Other beneficial effects, such as improved bud production, fruit quality, and yield, are also recognized . Since its wide application on various crops worldwide and side effects, such as potential endocrine‐disrupting properties, concerns have arisen regarding the potential risk to humans and wildlife from exposure to its residue and metabolites …”
Section: Introductionmentioning
confidence: 99%
“…Other beneficial effects, such as improved bud production, fruit quality, and yield, are also recognized. 2,[4][5][6][7] Since its wide application on various crops worldwide and side effects, such as potential endocrine-disrupting properties, concerns have arisen regarding the potential risk to humans and wildlife from exposure to its residue and metabolites. 8,9 Moreover, paclobutrazol is a chiral compound because of the presence of asymmetrically substituted carbon atoms in the triazole alkyl moiety.…”
Section: Introductionmentioning
confidence: 99%